Cationic electrodeposition coating composition, electrodeposition coated product, and method for producing electrodeposition coated product
The cationic electrodeposition coating composition, using aminated epoxy resin and niobium oxide sol, addresses the lack of rust prevention on untreated objects by forming a high-performance coating film without chemical conversion treatment, enhancing corrosion resistance and appearance on metal substrates.
Patent Information
- Application Number
- JP2023096686
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-25
AI Technical Summary
Cationic electrodeposition paints applied directly to untreated objects lack sufficient rust prevention properties without chemical conversion treatment.
A cationic electrodeposition coating composition containing aminated epoxy resin, niobium oxide sol or colloidal particles, and optional additives like blocked polyisocyanate curing agents, rust prevention adjuvants, and phosphoric acid compounds, which are applied without chemical conversion treatment to provide high rust prevention.
The composition forms a coating film with enhanced rust prevention properties on untreated metal substrates like galvanized steel and aluminum, demonstrating improved corrosion resistance and appearance.
Smart Images

Figure 2024178513000001 
Figure 2024178513000002 
Figure 2024178513000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a cationic electrodeposition coating composition, an electrodeposition coated article, and a method for producing an electrodeposition coated article. [Background technology]
[0002] Cationic electrocoating paints are widely used as undercoats for imparting rust-proofing to industrial products such as automobiles. Usually, the object to be coated with cationic electrocoating paint is immersed in an electrocoating paint bath after chemical conversion treatment, and then the object is used as the cathode and an electric current is applied to the object to be coated. From the viewpoint of process simplification and resource saving, it is considered that the object to be coated is directly subjected to cationic electrocoating without chemical conversion treatment, but the object not subjected to chemical conversion treatment tends to have insufficient rust-proofing even if cationic electrocoating is performed. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2005-36261 A Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a cationic electrodeposition coating composition which is capable of exhibiting high rust prevention properties without the need for chemical conversion treatment of the substrate. [Means for solving the problem]
[0005] In order to solve the above problems, the present invention provides the following aspects. [1] an aminated epoxy resin (A); A niobium compound (B), A cationic electrodeposition coating composition comprising: [2] The cationic electrodeposition coating composition according to [1], wherein the niobium compound (B) is a niobium oxide sol or niobium oxide colloidal particles obtained by stabilizing a niobium oxide sol. [3] The cationic electrodeposition coating composition according to [1] or [2], further comprising a blocked polyisocyanate curing agent (C). [4] The cationic electrodeposition coating composition according to [1] or [2], further comprising a rust-preventive auxiliary (D) selected from the group consisting of silica, a silane coupling agent, a titanium coupling agent, and mixtures thereof. [5] The cationic electrodeposition coating composition according to [1] or [2], further comprising a phosphoric acid compound (E). [6] The cationic electrodeposition coating composition according to [1] or [2], further comprising a polyamidine compound (F). [7] The polyamidine compound has the following general formula: [ka] (In the formula, R 1 and R 2 are each independently a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms, and X is an anion. The cationic electrodeposition coating composition according to [6], having a structural unit represented by the following formula: [8] The cationic electrodeposition coating composition according to [1] or [2], further comprising a pigment (G). [9] The cationic electrodeposition coating composition according to [1] or [2], further comprising a curing catalyst (H).
[10] The cationic electrodeposition coating composition according to [1] or [2], which is applied to a galvanized steel sheet, a cold-rolled steel sheet or an aluminum substrate without chemical conversion treatment.
[11] A coated object and An electrodeposition coated article having an electrodeposition coating film formed on the substrate using the cationic electrodeposition coating composition described in [1] or [2].
[12] A step of immersing a substrate in the cationic electrodeposition coating composition according to [1] or [2], and then applying a voltage between the substrate and a counter electrode to form an uncured electrodeposition coating film on the substrate; and heating the uncured electrodeposition coating film at a temperature of 75°C or higher and 200°C or lower to obtain a cured electrodeposition coating film. Effect of the Invention
[0006] According to the present invention, by blending a niobium oxide compound (particularly, niobium oxide sol or niobium oxide colloidal particles obtained by stabilizing the niobium oxide sol with citric acid or a salt thereof) into a cationic electrodeposition coating composition, it is possible to perform cationic electrodeposition coating without carrying out a chemical conversion treatment on a substrate (particularly, a zinc-plated steel sheet or an aluminum substrate) and form a coating film having high rust prevention properties. Furthermore, it is possible to provide an electrodeposition-coated article using the cationic electrodeposition coating composition of the present invention and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The cationic electrodeposition coating composition of the present invention is believed to exhibit rust prevention properties by depositing a metal (specifically, niobium) on a metal substrate when the metal substrate is immersed in a bath of the electrodeposition coating composition. This metal deposition may occur even without passing an electric current through the cationic electrodeposition bath, and it is believed that the metal deposition is accelerated when a current is passed through the cationic electrodeposition bath with the substrate as the cathode. The substrate is more specifically a galvanized steel sheet, a cold-rolled steel sheet, or an aluminum substrate, and a high rust prevention effect can be obtained without chemical conversion treatment or passing an electric current through the substrate.
[0008] [Cationic electrodeposition coating composition] The cationic electrodeposition coating composition according to this embodiment (hereinafter sometimes simply referred to as the coating composition) contains an aminated epoxy resin (A) and a niobium compound (B). The cationic electrodeposition coating composition of the present invention further contains a blocked polyisocyanate curing agent (C), a rust prevention auxiliary such as silica, a silane coupling agent, a titanium coupling agent or a mixture thereof (D), a phosphoric acid compound (E), a polyamidine compound (F), a pigment (G) or a curing catalyst (H), etc. Each component will be described below.
[0009] <Aminified epoxy resin (A)> The aminated epoxy resin (A) is a film-forming resin. The aminated epoxy resin is contained in the cationic electrodeposition coating composition in the form of a resin emulsion. In the aminated epoxy resin (A), at least one oxirane ring (also called "epoxy group") of the epoxy resin is aminated.
[0010] The number average molecular weight of the aminated epoxy resin (A) is, for example, 1,000 or more and 7,000 or less. When the number average molecular weight is 1,000 or more, the rust prevention and solvent resistance of the obtained cured electrodeposition coating film are likely to be improved. When the number average molecular weight is 7,000 or less, the viscosity of the aminated epoxy resin (A) can be easily adjusted, allowing for smooth synthesis, and in addition, the obtained aminated epoxy resin (A) can be easily emulsified and dispersed. The number average molecular weight of the aminated epoxy resin (A) may be 1,500 or more and 4,000 or less.
[0011] The number average molecular weight is a value calculated as a styrene homopolymer, measured by gel permeation chromatography.
[0012] The amine value of the aminated epoxy resin (A) is, for example, 20 mgKOH / g or more and 100 mgKOH / g or less. When the amine value of the aminated epoxy resin (A) is 20 mgKOH / g or more, the stability of the emulsion dispersion of the aminated epoxy resin (A) in the coating composition is good. When the amine value is 100 mgKOH / g or less, the amount of amino groups in the cured electrodeposition coating film becomes appropriate, and the decrease in the water resistance of the coating film is suppressed. The amine value of the aminated epoxy resin (A) may be 20 mgKOH / g or more and 80 mgKOH / g or less.
[0013] The amine value can be determined by the following method in accordance with ASTM D2073. (1) Accurately weigh out 500 mg of aminated epoxy resin into a 200 ml Erlenmeyer flask. (2) Add approximately 50 ml of glacial acetic acid and dissolve uniformly. (3) Add 5 to 6 drops of indicator (methyl violet solution) and stir evenly. (4) Titrate with 0.1N perchloric acid and acetic acid solution, and the endpoint is when the solution turns bright green. (The above (3) and (4) may be replaced by potentiometric titration.)
[0014] The hydroxyl value of the aminated epoxy resin (A) is, for example, 150 mgKOH / g or more and 650 mgKOH / g or less. When the hydroxyl value is 150 mgKOH / g or more, the curability of the coating composition is increased and the coating appearance is improved. When the hydroxyl value is 650 mgKOH / g or less, the amount of hydroxyl groups remaining in the cured electrodeposition coating film becomes appropriate, and the water resistance of the coating film is easily improved. The hydroxyl value of the aminated epoxy resin may be 150 mgKOH / g or more and 400 mgKOH / g or less.
[0015] The hydroxyl value can be determined by the neutralization titration method described in JIS K 0070 using an aqueous potassium hydroxide solution.
[0016] In particular, when the aminated epoxy resin (A) has a number average molecular weight in the range of 1,000 to 7,000, an amine value of 20 to 100 mgKOH / g, and a hydroxyl value of 150 to 650 mgKOH / g (preferably 150 to 400 mgKOH / g), the rust prevention properties of the coated article are likely to be further improved.
[0017] The coating composition may contain multiple aminated epoxy resins (A) with different amine values and / or hydroxyl values. In this case, the average amine value and average hydroxyl value calculated based on the mass ratio of the multiple aminated epoxy resins (A) are preferably within the above ranges. In particular, the multiple aminated epoxy resins (A) preferably contain two types of aminated epoxy resins, a first aminated epoxy resin having an amine value of 20 to 50 mgKOH / g and a hydroxyl value of 50 to 300 mgKOH / g, and a second aminated epoxy resin having an amine value of 50 to 200 mgKOH / g and a hydroxyl value of 200 to 500 mgKOH / g. The difference in amine value between the first and second aminated epoxy resins is preferably 10 to 100 mgKOH / g, and the difference in hydroxyl value is preferably 10 to 300 mgKOH / g. This makes the core part of the emulsion more hydrophobic and the shell part more hydrophilic, making it easier to improve the rust prevention properties of the coated article.
[0018] The aminated epoxy resin (A) is obtained by modifying the oxirane ring (also called "epoxy group") of an epoxy resin with an amine compound. As the amine compound, it is preferable to use an amine compound having at least one of a primary amino group, a secondary amino group, and a tertiary amino group, excluding ketimine (including diketimine).
[0019] In the amination, the amine compound is preferably used in an amount of 0.9 to 1.2 equivalents per equivalent of epoxy group in the raw material epoxy resin. The reaction conditions for the amination can be appropriately selected depending on the reaction scale, etc. For example, the reaction may be performed at 80°C to 150°C for 0.1 to 5 hours, or at 120°C to 150°C for 0.5 to 3 hours.
[0020] (Epoxy resin) The epoxy resin, which is the starting material of the aminated epoxy resin (A), is, for example, a polyphenol polyglycidyl ether type epoxy resin, which is a reaction product of a polycyclic phenol compound and epichlorohydrin. Examples of the polycyclic phenol compound include bisphenol A, bisphenol F, bisphenol S, phenol novolac, cresol novolac, etc. In this specification, the "polyphenol polyglycidyl ether type epoxy resin" includes a state in which a polyphenol polyglycidyl ether type epoxy resin and a polycyclic phenol compound are alternately and continuously reacted to extend the chain.
[0021] In the modification of an epoxy resin with an amine compound, it is preferable to use an epoxy resin obtained by a chain extension reaction of a polyphenol polyglycidyl ether type epoxy resin and a polycyclic phenol compound. The conditions of the chain extension reaction are not particularly limited and can be appropriately selected depending on the stirring device used, the reaction scale, etc. The reaction conditions can be, for example, 85 to 180°C and 0.1 to 8 hours. More preferably, the reaction conditions can be 100 to 150°C and 2 to 8 hours. The stirring device used is not particularly limited and can be a stirring device commonly used in the paint field.
[0022] In addition to the above, the epoxy resin may be an oxazolidone ring-containing epoxy resin described in JP-A-5-306327. These epoxy resins can be prepared by reacting a diisocyanate compound or a bis-urethane compound obtained by blocking the isocyanate group of a diisocyanate compound with a lower alcohol such as methanol or ethanol with epichlorohydrin.
[0023] The epoxy resin may be a resin obtained by subjecting a part of the epoxy resin to a chain extension reaction before modification with an amine compound. For example, bifunctional polyester polyol, polyether polyol, dibasic carboxylic acid, etc. may be used for the chain extension reaction. Examples of the polyether polyol include polyols having a polyethylene oxide group and polyols having a polypropylene oxide group. Thus, for example, when a chain extension reaction is performed using a polyol having a polypropylene oxide group, a polypropylene oxide group-containing epoxy resin is obtained. The content of the polypropylene oxide group-containing epoxy resin is preferably 1 to 40 parts by mass, more preferably 15 to 25 parts by mass, relative to 100 parts by mass of the epoxy resin. Examples of epoxy resins having the same aspect as the polypropylene oxide group-containing epoxy resin include epoxy resins obtained by a chain extension reaction of a polyphenol polyglycidyl ether type epoxy resin, a polycyclic phenol compound, and a polypropylene oxide group-containing epoxy resin.
[0024] The aminated epoxy resin (A) is obtained by reacting the epoxy groups of the epoxy resin with an amine compound. The epoxy groups of the epoxy resin are all consumed by the reaction with the amine compound, and substantially no epoxy groups remain in the molecule of the aminated epoxy resin (A).
[0025] (Amine compounds) Examples of amine compounds other than ketimines used for the conversion of epoxy resins to amino include primary amines such as butylamine, octylamine, and monoethanolamine; secondary amines such as diethylamine, dibutylamine, methylbutylamine, diethanolamine, and N-methylethanolamine; tertiary amines such as triethylamine, N,N-dimethylbenzylamine, and N,N-dimethylethanolamine; complex amines such as diethylenetriamine; diamines having a primary amino group and a tertiary amino group such as N,N-dimethyl-1,3-propanediamine and N,N-dimethylethylenediamine; diamines having a primary amino group, a tertiary amino group, and a hydroxyl group such as N-(3-aminopropyl)diethanolamine. The amine compounds may be used alone or in combination of two or more. Among them, the use of a diamine having a hydroxyl group tends to improve the adhesion and curability of the coating film.
[0026] In the amine compound, the number of primary amino groups is not particularly limited, and may be 1 or 2 or more. In particular, from the viewpoint of reaction control, the number of primary amino groups is preferably 1. The number of hydroxyl groups is also not particularly limited, and may be 1 or 2 or more.
[0027] (Other film-forming resins) The cationic electrodeposition coating composition may contain, as necessary, an aminated resin other than the aminated epoxy resin (A), such as an aminated acrylic resin or an aminated polyester resin. The coating composition may also contain another coating film-forming resin other than the above aminated resin. Examples of other coating film-forming resins include hydroxyl-containing acrylic resins, hydroxyl-containing polyester resins, urethane resins, butadiene resins, phenolic resins, and xylene resins. Of all the curable resins contained in the coating composition, 80% by mass or more, further 90% by mass or more, and particularly 100% by mass may be the aminated epoxy resin (A).
[0028] <Niobium Compound (B)> The niobium compound may be any compound containing niobium, but niobium oxide is generally used. In particular, niobium oxide sol is easily available. The niobium oxide sol is not particularly limited, and examples thereof include those produced by known methods described in Japanese Patent No. 2849799 and the like. Niobium oxide sol produced by Taki Chemical Co., Ltd. can also be used.
[0029] The above-mentioned niobium oxide sol can be produced, for example, by dissolving niobium oxide in hydrofluoric acid, adding it to aqueous ammonia, filtering and washing to obtain a niobium hydroxide slurry, adding oxalic acid dihydrate, then adding water, and allowing the reaction to proceed under reflux conditions while stirring to obtain a uniform solution of niobium oxide colloidal particles, and then adding citric acid or a salt thereof, followed by stirring and mixing. If necessary, a basic compound such as ammonia may be added to the obtained niobium oxide sol to adjust the pH to a desired level. It is possible to judge whether a uniform niobium oxide colloidal particle solution has been obtained by the color of the slurry liquid, and it can be judged that the liquid is in a uniform state when it is blue in color.
[0030] The niobium oxide sol that can be used in the cationic electrodeposition coating composition of the present invention may be a highly stabilized niobium oxide sol solution stabilized by oxalic acid by further adding citric acid. The cationic electrodeposition coating composition of the present invention can be prepared by diluting the above niobium oxide sol to a required concentration or mixing other components as necessary, and is stable for a long period of time after preparation without causing thickening, gelation, precipitation, etc. The important thing is that the niobium oxide sol used in the cationic electrodeposition coating composition of the present invention is in a state highly stabilized by citric acid or a salt thereof, and the amount of oxalic acid or a salt thereof blended during the production of the above niobium oxide sol is not particularly limited. This is preferable in that the stability of the niobium oxide colloidal particles does not decrease even when mixed with other components contained in the cationic electrodeposition coating composition of the present invention, such as a blocked polyisocyanate curing agent (C), a rust-preventive auxiliary agent (D) which is silica, a silane coupling agent, a titanium coupling agent, or a mixture thereof, a phosphoric acid compound (E), a polyamidine compound (F), a pigment (G), or a curing catalyst (H), etc.
[0031] The amount of citric acid or a salt thereof added to the cationic electrodeposition coating composition of the present invention is preferably within the range of a lower limit of 0.02 and an upper limit of 1.0 in terms of molar ratio relative to Nb in the cationic electrodeposition coating composition. If the amount of citric acid or a salt thereof added is less than 0.02 in terms of molar ratio, the stability when other components are added becomes insufficient, whereas if it exceeds 1.0, the stabilizing effect corresponding to the amount added is no longer obtained, which is uneconomical.
[0032] The niobium oxide colloidal particles preferably have an average particle size of 100 nm or less. The smaller the average particle size, the more stable and dense the niobium oxide treatment coating film is formed, so that the substrate can be stably provided with rust prevention properties. The average particle size of the niobium oxide colloidal particles can be measured using a particle size distribution measuring device using dynamic scattered light, such as NICOMP Model-370 (manufactured by PACIFIC SCIENTIFIC).
[0033] The cationic electrodeposition coating composition of the present invention preferably contains the above niobium oxide colloidal particles in an amount of 1% by mass or more based on the total non-volatile content of the cationic electrodeposition coating composition, when the Nb in the colloidal particles is converted into Nb2O5. If the above content is less than 1% by mass, sufficient rust prevention is not obtained, which is not preferable. The lower limit of the above content is more preferably 2% by mass, and even more preferably 3% by mass. The upper limit of the above content is more preferably 30% by mass, and even more preferably 15% by mass.
[0034] <Blocked polyisocyanate curing agent (C)> A blocked polyisocyanate curing agent (C) (hereinafter, sometimes simply referred to as curing agent (C)) may also be blended in the cationic electrodeposition coating composition. In cationic electrodeposition coating, the blocked polyisocyanate curing agent (C) usually reacts with reactive groups (specifically, hydroxyl groups or amino groups) in the aminated epoxy resin (A), which is a coating film-forming component, to form a cured coating film. However, even if the blocked polyisocyanate curing agent (C) is not present, the cationic electrodeposition coating composition of the present invention can be used as a so-called lacquer-like coating film formation (coating film formation without active curing reaction) in which niobium is precipitated on a metal substrate (particularly, a zinc-plated steel sheet, a cold-rolled steel sheet, or an aluminum substrate), and then an aminated epoxy resin is precipitated to form a coating film. Therefore, the blocked polyisocyanate curing agent (C) is described as an additive. Usually, a cationic electrodeposition coating composition contains a blocked polyisocyanate curing agent (C), and is often actively cured by heating.
[0035] The blocked polyisocyanate curing agent (C) can be prepared by blocking a polyisocyanate with a capping agent.
[0036] Examples of polyisocyanates include aliphatic diisocyanates such as hexamethylene diisocyanate (including trimer), tetramethylene diisocyanate, and trimethylhexamethylene diisocyanate; alicyclic polyisocyanates such as isophorone diisocyanate and 4,4'-methylenebis(cyclohexylisocyanate); and aromatic diisocyanates such as 4,4'-diphenylmethane diisocyanate, tolylene diisocyanate, and xylylene diisocyanate.
[0037] Examples of the sealing agent that can be preferably used include monovalent alkyl (or aromatic) alcohols such as n-butanol, n-hexyl alcohol, 2-ethylhexanol, lauryl alcohol, phenol carbinol, and methylphenyl carbinol; cellosolves such as ethylene glycol monohexyl ether and ethylene glycol mono 2-ethylhexyl ether; polyether-type both-terminal diols such as polyethylene glycol, polypropylene glycol, and polytetramethylene ether glycol phenol; polyester-type both-terminal polyols obtained from diols such as ethylene glycol, propylene glycol, and 1,4-butanediol and dicarboxylic acids such as oxalic acid, succinic acid, adipic acid, suberic acid, and sebacic acid; phenols such as para-t-butylphenol and cresol; oximes such as dimethyl ketoxime, methyl ethyl ketoxime, methyl isobutyl ketoxime, methyl amyl ketoxime, and cyclohexanone oxime; and lactams represented by ε-caprolactam and γ-butyrolactam.
[0038] The blocking rate of the blocked polyisocyanate curing agent (C) is preferably 100%, which improves the storage stability of the coating composition.
[0039] The content of the curing agent (typically, a blocked polyisocyanate curing agent (C)) is set in consideration of the amount, structure, etc. of the film-forming resin (typically, an aminated epoxy resin (A)). Specifically, a sufficient amount of the curing agent is used to react with active hydrogen-containing functional groups such as primary amino groups, secondary amino groups, and hydroxyl groups possessed by the film-forming resin. The curing agent is blended, for example, so that the solid content mass ratio of the film-forming resin to the curing agent (film-forming resin / curing agent) is 90 / 10 to 50 / 50, more preferably 80 / 20 to 65 / 35. The fluidity and curing speed of the coating composition are controlled by the solid content mass ratio of the film-forming resin to the curing agent.
[0040] The cationic electrodeposition coating composition may contain a curing agent other than the blocked polyisocyanate curing agent (C) as necessary. Examples of other curing agents include organic curing agents such as melamine resins or phenolic resins, and silane coupling agents, which are rust-preventive auxiliary agents described below as component (D). Of all the curing agents contained in the cationic electrodeposition coating composition, 80% by mass or more, further 90% by mass or more, particularly 100% by mass may be the blocked polyisocyanate curing agent (C).
[0041] <Anti-rust auxiliary (D) selected from the group consisting of silica, a silane coupling agent, a titanium coupling agent, and a mixture thereof> The cationic electrodeposition coating composition of the present invention may contain an anti-rust auxiliary (D) selected from the group consisting of silica, silane coupling agents, titanium coupling agents and mixtures thereof. These are used as anti-rust auxiliary agents because they synergistically improve the anti-rust performance when used in combination with the niobium compound (B). Examples of silica include normal water-dispersible silica.
[0042] The water-dispersible silica is not particularly limited, and examples thereof include spherical silica, chain silica, and aluminum-modified silica, which are low in impurities such as sodium. The spherical silica is not particularly limited, and examples thereof include colloidal silica such as "Snowtex N", "Snowtex O", "Snowtex OXS", and "Snowtex UP" (all manufactured by Nissan Chemical Industries, Ltd.), and fumed silica such as "Aerosil" (manufactured by Nippon Aerosil Co., Ltd.). The chain silica is not particularly limited, and examples thereof include silica gel such as "Snowtex PS-M" and "Snowtex PS-MO" (both manufactured by Nissan Chemical Industries, Ltd.). The aluminum-modified silica is, for example, commercially available silica gel such as "Adelite AT-20A" (manufactured by Asahi Denka Kogyo Co., Ltd.).
[0043] When the cationic electrodeposition coating composition of the present invention contains the above-mentioned water-dispersible silica, the SiO2 content in the cationic electrodeposition coating composition is preferably 30% by mass or less based on the total non-volatile content in the cationic electrodeposition coating composition. If it exceeds 30% by mass, there is a problem that the film becomes brittle and the rust prevention property decreases. The upper limit is more preferably 30% by mass, and even more preferably 3% by mass.
[0044] Silane coupling agents and titanium coupling agents are preferred in that they can improve adhesion to metal surfaces, and further act as crosslinking agents for the aminated epoxy resin (A), thereby improving corrosion resistance.
[0045] The silane coupling agent is not particularly limited, and examples thereof include vinyl methoxysilane, vinyl trimethoxysilane, vinyl ethoxysilane, vinyl triethoxysilane, 3-aminopropyl triethoxysilane, 3-glycidoxypropyl trimethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-mercaptopropyl trimethoxysilane, N-(1,3-dimethylbutylidene)-3-(triethoxysilyl)-1-propanamine, N,N'-bis[3-(trimethoxysilyl)propyl]ethylenediamine, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane. Examples of the silane include propyltrimethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, and N-[2-(vinylbenzylamino)ethyl]-3-aminopropyltrimethoxysilane.
[0046] Among them, particularly preferred silane coupling agents include vinyl methoxy silane, vinyl ethoxy silane, 3-aminopropyl triethoxy silane, 3-glycidoxypropyl trimethoxy silane, 3-methacryloxypropyl trimethoxy silane, 3-mercaptopropyl trimethoxy silane, N-(1,3-dimethylbutylidene)-3-(triethoxysilyl)-1-propanamine, and N,N'-bis[3-(trimethoxysilyl)propyl]ethylenediamine. The above silane coupling agents may be used alone or in combination of two or more.
[0047] The titanium coupling agent is not particularly limited, and examples thereof include isopropyl triisostearoyl titanate, isopropyl tri-n-dodecylbenzenesulfonyl titanate, isopropyl tris(dioctylpyrophosphate) titanate, tetraisopropyl bis(dioctylphosphite) titanate, tetraoctyl bis(ditridecylphosphite) titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(di-tridecyl)phosphite titanate, bis(dioctylpyrophosphate)oxyacetate titanate, bis(dioctylpyrophosphate)ethylene titanate, isopropyl trioctanoyl titanate, isopropyl dimethacryloyl isostearoyl titanate, isopropyl isostearoyl diacryl titanate, isopropyl tri(dioctylphosphate) titanate, and isopropyl tricumylphenyl. Titanate, isopropyl tri(N-aminoethyl-aminoethyl)titanate, tetraisopropyl titanate, tetra normal butyl titanate, butyl titanate dimer, tetrakis(2-ethylhexyl)titanate, tetrastearyl titanate, tetramethyl titanate, diethoxybis(acetylacetonato)titanium, diisopropylbis(acetylacetonato)titanium, diisopropoxybis(ethylacetoacetate)titanium, isopropoxy(2-ethyl-1,3-hexanediolato)titanium, di(2-ethylhexoxy)bis(2-ethyl-1,3-hexanediolato)titanium, di-n-butoxybis(triethanolaminato)titanium, tetraacetylacetonate titanium, hydroxybis(lactato)titanium, dicumylphenyloxyacetate titanate, diisostearoyl ethylene titanate, and the like.
[0048] The titanium coupling agent may be a commercially available product, such as KR-TTS, KR-46B, KR-55, KR-41B, KR-38S, KR-138S, KR-238S, 338X, KR44, KR9SA, etc., which are the Plainact series manufactured by Ajinomoto Fine-Techno Co., Ltd.; TA-10, TA-25, TA-22, TA-30, TC-100, TC-200, TC-401, TC-750, etc., which are the Orgatics series manufactured by Matsumoto Fine Chemical Co., Ltd.; and A-1, B-1, TOT, TST, TAA, TAT, TLA, TOG, TBSTA, A-10, TBT, B-2, B-4, B-7, B-10, TBSTA-400, TTS, TOA-30, TSDMA, TTAB, TTOP, etc., manufactured by Nippon Soda Co., Ltd.
[0049] When the cationic electrodeposition coating composition of the present invention contains the above-mentioned silane coupling agent or titanium coupling agent (sometimes simply referred to as "coupling agent"), the content of the silane coupling agent or titanium coupling agent is preferably within the range of a lower limit of 0.5% by mass and an upper limit of 30% by mass based on the total non-volatile content of the cationic electrodeposition coating composition. If the content of the coupling agent is less than 0.5% by mass, the rust prevention auxiliary function may be insufficient, and if it exceeds 30% by mass, the effect of adding the coupling agent becomes saturated and uneconomical, and gelation, thickening, etc. of the composition may occur, which is not preferable, and the liquid stability may decrease. The lower limit is more preferably 1% by mass, and the upper limit is more preferably 20% by mass.
[0050] <Phosphate Compounds (E)> The cationic electrodeposition coating composition of the present invention preferably contains a phosphoric acid compound (E). The phosphoric acid compound contained in the cationic electrodeposition coating composition of the present invention forms a metal phosphate on the surface of the substrate, thereby further improving the rust prevention of the surface treatment film.
[0051] The above-mentioned phosphate compound is not particularly limited as long as it is a compound that can form phosphate ions in water, and examples thereof include phosphoric acids (e.g., phosphorous acid, hypophosphorous acid, organic phosphoric acid, organic phosphorous acid, phosphoric acid, phosphonic acid, etc.); phosphates (e.g., Na3PO4, Na2HPO4, NaH2PO4, zinc phosphate, etc.); condensed phosphoric acids (e.g., condensed phosphoric acid, polyphosphoric acid, metaphosphoric acid, pyrophosphoric acid, and ultraphosphoric acid, etc.) or salts thereof.
[0052] When the cationic electrodeposition coating composition of the present invention contains the above phosphoric acid compound, the content of the phosphoric acid compound in the cationic electrodeposition coating composition is preferably within the range of a lower limit of 0.1 mass% and an upper limit of 20 mass% based on the total solid matter of the cationic electrodeposition coating composition. If the content is less than 0.1 mass%, the effect of improving corrosion resistance may not be sufficient, and if it exceeds 20 mass%, excessive etching of the zinc-based plated steel sheet or gelation of the composition may occur, which is not preferable. The lower limit is more preferably 0.5 mass%, and the upper limit is more preferably 10 mass%.
[0053] <Polyamidine Compounds (F)> The polyamidine compound (F) is added to improve the corrosion resistance of the edge portion of the metal substrate. Specifically, the polyamidine compound (F) is a cyclic polyamidine compound represented by the following general formula (I): [ka] (In the formula, R 1 and R 2 are each independently a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms, and X is an anion. The compound includes a structural unit having a cyclic amidine structure represented by the following formula:
[0054] Such polyamidine compounds having a cyclic structure are easily deposited on the edge portion because of their electric charge, and further increase the viscosity of the cationic electrodeposition coating composition, which is believed to improve the edge portion rust prevention.
[0055] R1 and R 2 may each independently be a hydrogen atom. X is, for example, a halogen ion. Examples of the halogen ion include F - , Cl - , Br - , I - Among them, halogen ions are Cl because they are easy to obtain. - It may be.
[0056] The cyclic polyamidine compound can be synthesized, for example, by hydrolyzing a copolymer of N-vinyl carboxylic acid amide and an unsaturated nitrile in the presence of an acid. During the hydrolysis in the presence of an acid, the amide group derived from the N-vinyl carboxylic acid amide is hydrolyzed and reacts with the cyano group of the unsaturated nitrile to form a cyclic amidine skeleton.
[0057] Examples of N-vinyl carboxylic acid amides include N-vinyl acetamide, N-vinyl-N-methyl acetamide, N-vinyl formamide, N-methyl-N-vinyl formamide, N-vinyl propionic acid amide, and N-vinyl butyric acid amide. These may be used alone or in combination of two or more.
[0058] The unsaturated nitrile may have, for example, 3 to 18 carbon atoms, or 3 to 9 carbon atoms. Specific examples of the unsaturated nitrile include acrylonitrile, α-alkyl acrylonitriles such as methacrylonitrile and ethacrylonitrile, fumaronitrile, and α-halogeno acrylonitriles such as α-chloro acrylonitrile and α-bromo acrylonitrile. These may be used alone or in combination of two or more.
[0059] The acid used for the hydrolysis is, for example, a strong inorganic acid, and specific examples thereof include hydrochloric acid, nitric acid, and p-toluenesulfonic acid.
[0060] The cyclic polyamidine compound may be a partial hydrolysis product of a copolymer of N-vinyl carboxylic acid amide and an unsaturated nitrile. Therefore, the cyclic polyamidine compound may be a copolymer of the above-mentioned constitutional unit (I) and, for example, a copolymer of the following two general formulas: [ka] [ka] (In the above two formulas, R 1 , R 2 and R 3 are each independently a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms.) When the structural units (II) and (III) are arranged as shown in the following chemical formula, the amidine structure of the structural unit (I) is obtained by hydrolysis: [ka] (In the formula, R 1 , R 2 and R 3 are each independently a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms.)
[0061] The number average molecular weight of the cyclic polyamidine compound is, for example, 50,000 or more. This allows the effect of improving edge rust prevention to be obtained with a small amount. The number average molecular weight of the cyclic polyamidine compound may be 80,000 or more, 100,000 or more, or 300,000 or more. The number average molecular weight of the cyclic polyamidine compound may be 4 million or less, 3.5 million or less, 3.2 million or less, or 3 million or less. In one embodiment, the number average molecular weight of the cyclic polyamidine compound may be 50,000 or more and 4 million or less, or 80,000 or more and 3.2 million or less.
[0062] The solid content mass of the polyamidine compound (F) may be 20 ppm or more of the solid content mass of the cationic electrodeposition coating composition. The solid content mass of the polyamidine compound (F) may be 1,200 ppm or less. Even if the amount of the polyamidine compound (F) added is so small, the effect of improving edge rust prevention can be obtained. The solid content mass of the polyamidine compound (F) may be 23 ppm or more, 25 ppm or more, or 50 ppm or more. The solid content mass of the polyamidine compound (F) may be 1,000 ppm or less, 700 ppm or less, or 200 ppm or less. In one embodiment, the solid content mass of the polyamidine compound (F) is 20 ppm or more and 1,200 ppm or less, may be 25 ppm or more and 1,000 ppm or less, may be 25 ppm or more and 700 ppm or less, or may be 50 ppm or more and 200 ppm or less.
[0063] <Pigment (G)> The pigment is a pigment that is generally used in cationic electrodeposition coating compositions. Examples of pigments include color pigments such as titanium white (titanium dioxide), zinc oxide, carbon black, and red iron oxide; extender pigments such as kaolin (e.g., calcined kaolin), talc, aluminum silicate, calcium carbonate, mica, and clay; and rust-preventive pigments such as iron phosphate, aluminum phosphate, calcium phosphate, aluminum tripolyphosphate, aluminum phosphomolybdate, and aluminum zinc phosphomolybdate. The coating composition may contain an extender pigment in order to further improve edge rust prevention.
[0064] The solid content of the cationic electrodeposition coating composition means all the components contained in the coating composition that remain in a solid form even after removal of the solvent. The pigment is usually added to the cationic electrodeposition coating composition as a pigment dispersion paste containing a pigment dispersion resin and a pigment.
[0065] (Pigment dispersion resin) The pigment dispersion resin is a resin for dispersing pigments. Examples of the pigment dispersion resin include pigment dispersion resins having cationic groups, such as modified epoxy resins having at least one selected from quaternary ammonium groups, tertiary sulfonium groups, and primary amino groups. Specific examples of the pigment dispersion resin include quaternary ammonium group-containing epoxy resins and tertiary sulfonium group-containing epoxy resins. Examples of the aqueous solvent include ion-exchanged water and ion-exchanged water containing a small amount of alcohols.
[0066] <Curing catalyst (H)> The cationic electrodeposition coating composition may contain a curing catalyst. The curing catalyst is not particularly limited, and any known catalyst in the coating field can be used. Examples of the curing catalyst include organic tin compounds and bismuth compounds. Examples of the organic tin compounds include dibutyltin oxide, dioctyltin oxide, dioctyltin dilaurate, dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin diacetate, dibutyltin dibenzoate, and dioctyltin dibenzoate. Examples of the bismuth compounds include bismuth oxide, bismuth hydroxide, bismuth subsalicylate, and bismuth subnitrate.
[0067] From the viewpoint of environmental burden, the content of the curing catalyst (particularly, the organotin compound) may be 0.5 mass % or less, or may be 0.25 mass % or less, of the solid content of the coating composition.
[0068] <Other ingredients> The coating composition may contain additives commonly used in the coating field, such as organic solvents, surfactants such as drying inhibitors and defoamers, viscosity modifiers such as acrylic resin particles, anti-repellent agents, and inorganic rust inhibitors, as necessary. Examples of organic solvents include ethylene glycol monobutyl ether, ethylene glycol monohexyl ether, ethylene glycol monoethylhexyl ether, propylene glycol monobutyl ether, dipropylene glycol monobutyl ether, and propylene glycol monophenyl ether. Examples of inorganic rust inhibitors include vanadium salts, copper salts, iron salts, manganese salts, magnesium salts, and calcium salts.
[0069] Furthermore, in addition to the above, known auxiliary complexing agents, buffering agents, smoothing agents, stress relaxation agents, gloss agents, semi-gloss agents, antioxidants, ultraviolet absorbing agents, and the like may be included depending on the purpose.
[0070] <Preparation of cationic electrodeposition coating composition> The coating composition is prepared by mixing a film-forming resin (typically, an aminated epoxy resin (A)) and a niobium compound (B), and, if necessary, other additive components, specifically, a blocked polyisocyanate curing agent (C), a rust-preventive auxiliary such as silica, a silane coupling agent, a titanium coupling agent or a mixture thereof (D), a phosphate compound (E), a polyamidine compound (F), a pigment (G) or a curing catalyst (H), etc., by a commonly used method.
[0071] The other components and additive components may be added to the resin emulsion, may be added to the pigment dispersion paste, or may be added during or after mixing of the resin emulsion and the pigment dispersion paste.
[0072] (Preparation of Resin Emulsion) The resin emulsion can be prepared by dissolving the aminated epoxy resin (A) and other film-forming resins, as well as the blocked polyisocyanate curing agent (C) and other curing agents, in an organic solvent to prepare solutions, mixing these solutions, and then neutralizing the mixture with a neutralizing acid.
[0073] Examples of the neutralizing acid include organic acids such as methanesulfonic acid, sulfamic acid, lactic acid, dimethylolpropionic acid, formic acid, acetic acid, etc. The neutralizing acid may be one or more selected from the group consisting of formic acid, acetic acid, and lactic acid.
[0074] The solid content of the resin emulsion may be, for example, 25% by mass or more and 50% by mass or less, and 35% by mass or more and 45% by mass or less, based on the total amount of the resin emulsion. The solid content of the resin emulsion means all of the components contained in the resin emulsion that remain in a solid form even after the solvent is removed. Specifically, the solid content of the resin emulsion means the aminated epoxy resin (A), the blocked polyisocyanate curing agent (C), and other solid components added as necessary, which are contained in the resin emulsion.
[0075] The amount of neutralizing acid used may be 10% or more and 100% or less, or 20% or more and 70% or less, in terms of the equivalent ratio of the neutralizing acid to the equivalent of the amino group in the aminated epoxy resin. Hereinafter, the equivalent ratio of the neutralizing acid to the equivalent of the amino group in the aminated epoxy resin is referred to as the neutralization rate. A neutralization rate of 10% or more ensures affinity to water and provides good water dispersibility.
[0076] (Method of preparing pigment dispersion paste) The pigment dispersion paste is prepared by mixing a pigment dispersion resin, a solid substance such as a pigment (in the present invention, any one or a mixture of the niobium compound (B), the rust prevention auxiliary (D), the phosphate compound (E), the pigment (G) and the curing catalyst (H)), and, if necessary, a polyamidine compound (F). The solid content by mass of the pigment dispersion resin in the pigment dispersion paste is not particularly limited, and may be, for example, 20 parts by mass or more and 100 parts by mass or less per 100 parts by mass of the pigment.
[0077] The solid content mass of the pigment dispersion paste is, for example, from 40% by mass to 70% by mass, and may be from 50% by mass to 60% by mass.
[0078] The solid content of the pigment dispersion paste means all components contained in the pigment dispersion paste that remain in a solid form even after removal of the solvent, specifically, the pigment dispersion resin, the pigment, and other solid components added as necessary, contained in the pigment dispersion paste.
[0079] [Method of manufacturing electrodeposition-coated products] An electrodeposition coating film is formed by electrocoating a substrate with the coating composition. An electrodeposition-coated article having an electrodeposition coating film is produced by a method (production method 1) comprising the steps of immersing an article to be coated in the cationic electrodeposition coating composition according to this embodiment, applying a voltage between the article to be coated and a counter electrode to form an uncured electrodeposition coating film on the article to be coated, and heating the coating film at a temperature of 75°C or higher and 200°C or lower to obtain a cured electrodeposition coating film.
[0080] As described above, the cationic electrodeposition coating composition contains the aminated epoxy resin (A), the niobium compound (B), and, if necessary, additive components (a blocked polyisocyanate curing agent (C), a rust prevention auxiliary (D), a phosphoric acid compound (E), a polyamidine compound (F), a pigment (G), a curing catalyst (H), or a combination thereof).
[0081] (1) Formation of uncured electrocoating film After immersing the substrate in the cationic electrodeposition coating composition, a voltage is applied between the substrate (cathode) and a counter electrode (anode), causing an uncured electrodeposition coating to be deposited on the substrate.
[0082] (Applied conditions) The voltage is, for example, 50 V or more and 450 V or less. The bath liquid temperature is, for example, 10° C. or more and 45° C. or less. The time for which the voltage is applied is not particularly limited, and is, for example, 2 minutes or more and 5 minutes or less.
[0083] (subject to be coated) The material of the substrate is not particularly limited as long as it can be electrically conductive. The shape of the substrate is not particularly limited either, and may be flat or have a complex three-dimensional shape. Examples of substrates include cold-rolled steel sheets, hot-rolled steel sheets, stainless steel, electrogalvanized steel sheets, hot-dip galvanized steel sheets, zinc-aluminum alloy-based plated steel sheets, zinc-iron alloy-based plated steel sheets, zinc-magnesium alloy-based plated steel sheets, zinc-aluminum-magnesium alloy-based plated steel sheets, aluminum-based plated steel sheets, aluminum-silicon alloy-based plated steel sheets, tin-based plated steel sheets, and those that have been subjected to chemical conversion treatment (for example, surface treatment using phosphates, zirconium salts, etc.). When chemical conversion treatment is performed using phosphates, the substrate may be surface-conditioned with a zinc-based, titanium-based, or manganese-based surface conditioner before chemical conversion treatment. This makes the crystals of the zinc phosphate coating more dense. In the present invention, the substrate is not chemically treated, and in particular, zinc-plated steel sheets and aluminum substrates can be used as they are without chemical conversion treatment. By using the material without chemical conversion treatment, the chemical conversion treatment step can be omitted, which is very advantageous.
[0084] (2) Hardening of electrodeposition coating The formed uncured electrodeposition coating film is washed with water if necessary, and then heated at a temperature of 75° C. to 200° C. This causes a curing reaction to occur, resulting in a cured electrodeposition coating film.
[0085] (Curing conditions) The curing temperature may be 100° C. or higher, or 110° C. or higher. The curing temperature may be, for example, 180° C. or lower, or 150° C. or lower. The heating time is not particularly limited, and is, for example, 10 to 30 minutes.
[0086] [Electrodeposition coating] The electrodeposition-coated product has a substrate and an electrodeposition coating film formed on the substrate by the cationic electrodeposition coating composition. The electrodeposition coating film is cured. The electrodeposition-coated product is produced, for example, by the method described above. The electrodeposition-coated product has excellent rust prevention properties. The electrodeposition-coated product further has a good appearance.
[0087] From the viewpoint of rust prevention, the thickness of the electrodeposition coating film after curing may be 5 μm or more and 60 μm or less. The thickness of the electrodeposition coating film after curing may be 10 μm or more. The thickness of the electrodeposition coating film after curing may be 25 μm or less. EXAMPLES
[0088] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited thereto. In the examples, "parts" and "%" are by weight unless otherwise specified.
[0089] [Production Example 1] Production of aminated epoxy resin (A1) Into a reaction vessel, 26 parts of butyl cellosolve, 940 parts of bisphenol A type epoxy resin (trade name DER-331J, manufactured by Dow Chemical Co.), 380 parts of bisphenol A, 58 parts of phenol, and 2 parts of dimethylbenzylamine were added, and the internal temperature was maintained at 120°C. After the reaction was continued until the epoxy equivalent reached 1100 g / eq, the reaction vessel was cooled until the temperature inside the reaction vessel reached 110°C. 60 parts of diethanolamine (DETA), 20 parts of N-methylethanolamine (MMA), and 85 parts of diethylenetriamine diketimine (diketimine: methyl isobutyl ketone solution with a solid content of 73%) were added, and the mixture was reacted at 140°C for 1 hour to obtain an aminated epoxy resin.
[0090] [Production Example 2] Production of aminated epoxy resin (A2) In a reaction vessel equipped with a stirrer, a cooling tube, a nitrogen inlet tube and a thermometer, 198 parts by mass of DER-331J (manufactured by Dow Chemical Company, diglycidyl ether of bisphenol A) and 108 parts by mass of bisphenol A were placed and dissolved in 45.7 parts by mass of DPnB (propylene glycol monobutyl ether) and 56.5 parts by mass of methyl isobutyl ketone (MIBK). 0.8 parts by mass of dimethylbenzylamine was added thereto, and the reaction was continued at 120°C until the epoxy equivalent reached 4,000, to obtain an epoxy resin having a bisphenol skeleton as a raw material. After the reaction was completed, 62.5 parts by mass of DPnB and 34.9 parts by mass of ketimine were added, and the reaction was continued at 120°C for 1 hour to obtain an aminated epoxy resin having a bisphenol skeleton (A2).
[0091] The resulting aminated epoxy resin had a number average molecular weight of 6,000. The obtained amine-modified epoxy resin (A2) was added to a mixed liquid of 5.2 parts by mass of 90% acetic acid and 482.5 parts by mass of ion-exchanged water and thoroughly stirred, and then 163.3 parts by mass of the mixture of MIBK and water was distilled off under reduced pressure at 50° C. to obtain an aqueous dispersion of aminated epoxy resin (A2) (solid content concentration: 38% by mass).
[0092] [Production Example 3] Production of blocked polyisocyanate curing agent (C) 1370 parts of polymethylene polyphenyl polyisocyanate (polymeric MDI) and 732 parts of methyl isobutyl ketone (MIBK) were charged into a reaction vessel and heated to 60°C. 300 parts of butyl diglycol ether and 1330 parts of butyl cellosolve were added dropwise at 60°C over 2 hours. After further heating at 75°C for 4 hours, it was confirmed that the absorption due to the isocyanate group disappeared in the measurement of the IR spectrum. After cooling, 27 parts of MIBK were added to obtain a blocked polyisocyanate curing agent (C).
[0093] [Production Example 4] Preparation of pigment dispersing resin In a reaction vessel equipped with a stirrer, a cooling tube, a nitrogen inlet tube and a thermometer, 2220 parts of isophorone diisocyanate and 342.1 parts of methyl isobutyl ketone were charged. The temperature was raised to 50°C, 2.2 parts of dibutyltin laurate were further charged, the temperature was raised to 60°C, and 878.7 parts of methyl ethyl ketone oxime were further charged. After that, the mixture was kept at 60°C for 1 hour, and it was confirmed that the NCO equivalent was 348, and 890 parts of dimethylethanolamine were further charged. The mixture was further kept at 60°C for 1 hour, and it was confirmed by IR that the NCO peak had disappeared. Next, while cooling so as not to exceed 60°C, 1872.6 parts of 50% lactic acid and 495 parts of deionized water were charged to obtain a quaternizing agent.
[0094] 870 parts of tolylene diisocyanate and 49.5 parts of methyl isobutyl ketone were charged into a different reaction vessel. While cooling so that the temperature did not exceed 50°C, 667.2 parts of 2-ethylhexanol were added dropwise to the reaction vessel over 2.5 hours. After completion of the dropwise addition, 35.5 parts of methyl isobutyl ketone were added and kept warm for 30 minutes. After that, it was confirmed that the NCO equivalent was 330 to 370, and a half-blocked polyisocyanate was obtained.
[0095] In a reaction vessel equipped with a stirrer, a cooling tube, a nitrogen inlet tube and a thermometer, 940.0 parts of bisphenol A type epoxy resin (trade name DER-331J, manufactured by Dow Chemical Co.) and 38.5 parts of methanol were charged, and 0.1 parts of dibutyltin dilaurate were further added. After heating this to 50°C, 87.1 parts of tolylene diisocyanate were added. The temperature was further raised to 100°C, and 1.4 parts of N,N-dimethylbenzylamine were added, and then the mixture was kept warm at 130°C for 2 hours. At this time, methanol was fractionated using a fractionating tube. This was cooled to 115°C, and methyl isobutyl ketone was added until the solid content concentration reached 90%. Then, 270.3 parts of bisphenol A and 39.2 parts of 2-ethylhexanoic acid were charged, and the mixture was heated and stirred at 125°C for 2 hours. Next, 516.4 parts of the half-blocked polyisocyanate were dropped over 30 minutes, and the mixture was heated and stirred for 30 minutes. Further, 1506 parts of polyoxyethylene bisphenol A ether was gradually added and dissolved therein. After cooling to 90°C, the above-mentioned quaternizing agent was added and the temperature was maintained at 70 to 80°C. After that, it was confirmed that the acid value was 2 or less, and a pigment dispersion resin (resin solid content 30%) was obtained.
[0096] [Preparation Example 1] Preparation of pigment dispersion paste A 116.7 parts of ion-exchanged water, 15.7 parts of 50% lactic acid aqueous solution, and 20.3 parts of bismuth oxide were stirred and mixed in a sand grinding mill. 169.4 parts of the pigment dispersion resin obtained in Production Example 4 and 0.7 parts of a polyoxyalkylene-type nonionic surfactant were added thereto, and the mixture was stirred at 60°C for 1 hour at 3000 rpm with a dissolver. Next, 338.7 parts of the pigment dispersion resin were added and stirred, and then 6.8 parts of zinc oxide, 67.7 parts of carbon black, and 264.1 parts of calcined kaolin, which are pigments, were added, and the mixture was dispersed using a sand mill at 40°C for 20 minutes at 1800 rpm until the particle size became 10 μm or less, to obtain a pigment paste A with a solid content concentration of 53% by mass.
[0097] [Preparation Example 2] Preparation of pigment dispersion paste B In a sand grinding mill, 117 parts of ion-exchanged water, 15.7 parts of 50% lactic acid aqueous solution, and 20.3 parts of bismuth oxide were stirred and mixed. 169.4 parts of the pigment dispersion resin obtained in Production Example 4 and 0.7 parts of a polyoxyalkylene-type nonionic surfactant were added thereto, and the mixture was stirred at 60°C for 1 hour at 3000 rpm with a dissolver. Next, 338.7 parts of the pigment dispersion resin were added and stirred, and then 6.8 parts of zinc oxide, 67.7 parts of carbon, 237.7 parts of calcined kaolin, and 26.4 parts of pigment silica were added, and the mixture was dispersed using a sand mill at 40°C for 20 minutes at 1800 rpm until the particle size became 10 μm or less, to obtain a pigment paste B with a solid content concentration of 53% by mass.
[0098] [Preparation Example 3] Manufacture of pigment dispersion paste C 117 parts of ion-exchanged water, 15.7 parts of 50% lactic acid aqueous solution, and 20.3 parts of bismuth oxide were stirred and mixed in a sand grinding mill. 169.4 parts of the pigment dispersion resin obtained in Production Example 4 and 0.7 parts of a polyoxyalkylene-type nonionic surfactant were added thereto, and the mixture was stirred at 60°C for 1 hour at 3000 rpm with a dissolver. Next, 338.7 parts of the pigment dispersion resin were added and stirred, and then 6.8 parts of zinc oxide pigment, 67.7 parts of carbon, 237.7 parts of calcined kaolin, and 26.4 parts of a zinc phosphate-based rust-preventive pigment (trade name LF Bousei PW-2, manufactured by Kikuchi Color Co., Ltd.) were added, and the mixture was dispersed using a sand mill at 40°C for 20 minutes at 1800 rpm until the particle size became 10 μm or less, and a pigment paste B with a solid content concentration of 53% by mass was obtained.
[0099] [Example 1] (Preparation of Resin Emulsion) 450 parts (solid content) of the aminated epoxy resin (A1) obtained in Production Example 1 and 240 parts (solid content) of the blocked polyisocyanate curing agent (C) obtained in Production Example 2 were mixed, and ethylene glycol mono-2-ethylhexyl ether was added so that the amount was 0.7% (4.5 parts) based on the solid content. Next, acetic acid was added to neutralize the mixture so that the neutralization rate was 45%, and ion-exchanged water was added to slowly dilute the mixture to obtain a resin emulsion.
[0100] (Production of cationic electrodeposition coating composition) A stainless steel container was charged with 654.4 parts of ion-exchanged water, 687.8 parts of emulsion of amine-modified epoxy resin (A1), 157.8 parts of pigment dispersion paste, and 3.57 parts of niobium oxide sol (Nb2O5; 6%, average particle size 5 nm, pH 8, NH3 / niobium oxide (Nb2O5) (molar ratio) = 0.5 to 1.5, manufactured by Taki Chemical Co., Ltd.) and mixed, and then aged at 40°C for 16 hours to obtain cationic electrodeposition coating composition A1.
[0101] (2) Preparation of electrocoated objects The cold-rolled steel sheet, the galvanized steel sheet, and the aluminum substrate were degreased by immersing them in Surf Cleaner EC90 (manufactured by Nippon Paint Co., Ltd.) at 50° C. for 2 minutes, and then rinsed with deionized water.
[0102] A necessary amount of ethylene glycol monohexyl ether was added to the cationic electrodeposition coating composition A1 so that the thickness of the electrodeposition coating film after curing was 20 μm, and then a zinc-plated steel sheet and an aluminum substrate were immersed in the mixture, and a voltage was applied under the conditions of increasing the voltage for 30 seconds, and then maintaining the voltage for 150 seconds after reaching the voltage under the conditions of each example, to deposit an uncured electrodeposition coating film on the substrate. The obtained uncured electrodeposition coating film was heat-cured at 160° C. for 15 minutes to obtain an electrodeposition-coated product having a cured electrodeposition coating film with a thickness of 20 μm.
[0103] The obtained coated objects (cold-rolled steel sheet, galvanized steel sheet, and aluminum substrate) were subjected to corrosion tests (cyclic corrosion tests) and evaluation of appearance by the methods described below. The results are shown in Table 1. Table 1 also shows the blend amounts of the components used (values converted into mass% of the added amount). In Table 1, "appearance" was evaluated for both the galvanized steel sheet and the aluminum substrate as coated objects, but since the results were the same, they are not listed separately for each coated object.
[0104] <Cycle Corrosion Test (CCT)> Using both electrocoated zinc-plated steel sheets and aluminum substrates, cross-cut scratches were made with a knife in the coating of the hardened electrocoated sheets so as to reach the substrate, and JASOM609-91 "Corrosion Test Method for Automotive Materials" was run for 100 cycles. After that, the occurrence of rust and blisters from the cross-cut areas was observed, and the corrosion resistance in accordance with an actual corrosive environment was evaluated for both the zinc-plated steel sheets and the aluminum substrate. The evaluation criteria were as follows: Evaluation criteria 5: The maximum width of rust or swelling is less than 7.5 mm from the cut area (both sides). No blisters except at the cut area. 4: The maximum width of the rust or blister is 5mm to 6mm from the cut area (both sides). There are blisters other than the cut area. 3: The maximum width of the rust or blister is 6mm or more but less than 10mm from the cut part (both sides) 2: The maximum width of the rust or blister is 10mm or more but less than 12.5mm from the cut part (both sides) 1: The maximum width of the rust or blister is 12.5 mm or more from the cut part (on both sides) A passing grade is 3 or above.
[0105] <Appearance> The arithmetic mean roughness (Ra) of the roughness curve of the cured electrodeposition coating was measured using an evaluation type surface roughness measuring instrument (Mitsutoyo, SURFTEST SJ-201P) according to the method of JIS-B0601. Seven measurements were made using a sample with a 2.5 mm width cutoff (number of sections: 5), and the Ra value (μm) was obtained by averaging the top and bottom erase values. The smaller the Ra value, the less unevenness there is and the better the coating appearance. 5: When Ra is less than 0.2 μm 4: When Ra is 0.2μm or more and less than 0.3μm 3: When Ra is between 0.3μm and less than 0.4μm 2: When Ra is 0.4μm or more and less than 0.5μm 1: When Ra is 0.5 μm or more.
[0106] [Example 2] In the same manner as in Example 1, a cationic electrodeposition coating composition was obtained, and electrodeposition coating was performed on a zinc-plated steel sheet and an aluminum substrate to produce an electrodeposition-coated product. The zinc-plated steel sheet and aluminum substrate, which were the coated products, were degreased by immersing them in Surf Cleaner EC90 (manufactured by Nippon Paint Surf Chemicals) at 50°C for 2 minutes, and then immersed in Surf Fine GL1 (manufactured by Nippon Paint Surf Chemicals) at room temperature for 30 seconds to condition the surface, and then immersed in Surf Dyne SD-5000 (manufactured by Nippon Paint Surf Chemicals), a zinc phosphate conversion treatment solution, at 40°C for 2 minutes. Thereafter, the product was washed with deionized water. The obtained electrodeposition-coated product was subjected to a cyclic corrosion test and evaluated for appearance in the same manner as in Example 1. The results are shown in Table 1.
[0107] [Example 3] In the same manner as in Example 1, cationic electrodeposition coating compositions were prepared in the amounts shown in Table 1, and were applied to a zinc-plated steel sheet and an aluminum substrate to prepare electrodeposition-coated articles. The obtained electrodeposition-coated articles were subjected to a cyclic corrosion test and evaluated for appearance in the same manner as in Example 1. Example 3 is an experiment that does not contain pigment (G). The results are shown in Table 1.
[0108] [Examples 4 to 10] In the same manner as in Example 1, cationic electrodeposition coating compositions were prepared in the amounts shown in Table 1, and were applied to zinc-plated steel sheets and aluminum substrates to prepare electrodeposition-coated articles. The obtained electrodeposition-coated articles were subjected to a cyclic corrosion test and evaluated for appearance in the same manner as in Example 1. The results are shown in Table 1. [Example 11] To the composition of Example 1, a 2% aqueous solution of polyamidine compound (F) (Himoc ZP-700, Himo Co., Ltd., number average molecular weight 3 million, partial hydrolysate of acrylonitrile-N-vinylformamide copolymer) was further added so that the solid content was 0.1 parts by mass of the solid content of the cationic electrodeposition coating composition, and the solution was applied to the substrate shown in Table 1 to prepare an electrodeposition coating. The obtained electrodeposition coating was subjected to a cyclic corrosion test and evaluated for appearance in the same manner as in Example 1. The results are shown in Table 1.
[0109] [Comparative Examples 1 to 4] A cationic electrodeposition coating composition was obtained in the same manner as in Example 1, except that the niobium compound (B) was not added and the components shown in Table 1 were used. The obtained cationic electrodeposition coating composition was applied to a galvanized steel sheet and an aluminum substrate to produce an electrodeposition coated product. Comparative Examples 1 and 2 are examples that do not contain a niobium compound, corresponding to Examples 1 and 2. Comparative Example 3 is an example in which a compound containing vanadium was used instead of a niobium compound, and Comparative Example 4 is an example in which a compound containing yttrium was used. The obtained electrodeposition coated article was subjected to a cyclic corrosion test and its appearance was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0110] [Table 1]
[0111] The ingredients used in Table 1 are as follows: Niobium oxide colloidal particles: Niobium oxide colloidal particle water dispersion (Nb2O5; 10%, average particle size: 2000 nm). Silane coupling agent: KBM403, 3-glycidoxypropyltrimethoxysilane; manufactured by Shin-Etsu Chemical Co., Ltd. Silica: Silica 550 (silicon dioxide (non-crystalline); manufactured by Fuji Silysia Chemical Co., Ltd.) Titanium coupling agent: Orgatix TC400 (titanium triethanolamine; Ti; 10.4%; solid content equivalent); manufactured by Matsumoto Fine Chemical Co., Ltd. Phosphonic acids: Reagents. Zinc phosphate-based anti-rust pigment: LF BOSEI PW-2 (zinc phosphate); manufactured by Kikuchi Color Co., Ltd. Polyamidine compound (F): Himoloc ZP-700, number average molecular weight 3 million, partial hydrolysis product of acrylonitrile-N-vinylformamide copolymer, ratio of structural unit (I) to structural unit (I+II): (I) / (I+II)=30-40% (molar ratio); Himo Co., Ltd. In the chemical formula of structural unit (I), R 1 and R 2 are both hydrogen and X represents chlorine. Ammonium metavanadate (V; 43.6%): Reagent. Yttrium nitrate: Reagent.
[0112] In all cases where the cationic electrodeposition coating compositions of the Examples were used, the cyclic corrosion test showed a rating of 3 or higher, indicating high rust prevention. Comparative Example 1, which is similar to Example 1 and does not contain a niobium compound, showed poor values in the cyclic corrosion test, especially for zinc-plated steel sheets. Comparative Example 2 used a zinc phosphate treatment (rust prevention treatment) for the pretreatment of the substrate, and therefore showed excellent rust prevention performance for both zinc-plated steel sheets and aluminum substrates. Comparative Examples 3 and 4 used a compound containing vanadium or a compound containing yttrium instead of a niobium compound, but did not provide excellent rust prevention performance for these metals. [Industrial Applicability]
[0113] The cationic electrodeposition coating composition of the present invention provides a coating film having excellent rust prevention properties and appearance.
Claims
1. an aminated epoxy resin (A); A niobium compound (B), A cationic electrodeposition coating composition comprising:
2. 2. The cationic electrodeposition coating composition according to claim 1, wherein said niobium compound (B) is a niobium oxide sol or niobium oxide colloidal particles obtained by stabilizing a niobium oxide sol.
3. 3. The cationic electrodeposition coating composition according to claim 1, further comprising a blocked polyisocyanate curing agent (C).
4. 3. The cationic electrodeposition coating composition according to claim 1 or 2, further comprising a rust-preventive auxiliary (D) selected from the group consisting of silica, a silane coupling agent, a titanium coupling agent and mixtures thereof.
5. 3. The cationic electrodeposition coating composition according to claim 1, further comprising a phosphoric acid compound (E).
6. 3. The cationic electrodeposition coating composition according to claim 1 or 2, further comprising a polyamidine compound (F).
7. The polyamidine compound has the following general formula: 【Chemistry 1】 (In the formula, R 1 and R 2 are each independently a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms, and X is an anion.
7. The cationic electrodeposition coating composition according to claim 6, which has a structural unit represented by the following formula:
8. 3. The cationic electrodeposition coating composition according to claim 1 or 2, further comprising a pigment (G).
9. 3. The cationic electrodeposition coating composition according to claim 1 or 2, further comprising a curing catalyst (H).
10. 3. The cationic electrodeposition coating composition according to claim 1 or 2, which is applied to a galvanized steel sheet, a cold-rolled steel sheet or an aluminum substrate without chemical conversion treatment.
11. A coated object and 3. An electrodeposition coated article comprising an electrodeposition coating film formed on the substrate from the cationic electrodeposition coating composition according to claim 1 or 2.
12. A step of immersing a substrate in the cationic electrodeposition coating composition according to claim 1 or 2, and then applying a voltage between the substrate and a counter electrode to form an uncured electrodeposition coating film on the substrate; and heating the uncured electrodeposition coating film at a temperature of 75° C. or higher and 200° C. or lower to obtain a cured electrodeposition coating film.
Citation Information
Patent Citations
Metal surface treatment composition, metal surface treatment method, and galvanized steel sheet
JP2005036261A
